Proposição de um novo modelo para a simulação computacional da cavitação resultante do golpe de ariete em adutoras - Paiva, Bruno Araújo (2019)
In the transient state of a system, the occurrence of vapor pressure can be found in such as low system load, high system peaks or transient production. With this, a vapor cavity is produced in the flow, possibly causing a column separation in the liquid. Subsequently, at the meeting of the liquid, high pressures are formed, significantly damaging the piping. THE cavitation is debated and studied until the present day, even with several developed researches, because there are some models that require hard data to be acquired, becoming when a computational simulation is to be performed. The method used in the This work is based on the method of the simple model, which is called the discrete gas cavity model. The model used, if compared to others, such as, discrete steam cavity model, column separation with constant wave velocity and no air release is much more intuitive and easy computational simulation, however, its main deficiency lies in the numerical oscillations that tend to be less damped. Therefore, this cavitation model can be transient phenomenon, since it always adopts the minimum pressure load equal to Steam pressure. In addition, to facilitate the modeling and general exposition of the analysis transient, it was considered a void within the system, thus modifying the analysis, because Gas and steam were previously analyzed inside the system. The method of cavitation in the software called UFC7, giving support for validation with the data available in the works of Nguyen, Bergant and Pezzinga. That in turn, showed to be very close, comparing with the graphs of each node contained in the model. However, with the computational numerical modeling of cavitation, the results were because the numerical method presented pressure to the experimental data, forming a final product of proven validity.